Fortress Introduction to Salvation and the Cross - Brondos, David A., 1958- (Book collections on Project MUSE., 2008)
What does it mean to be saved, and how can we make sense of the Christian claim that Christ died for our sins? That is the work of soteriology, the classic discipline of theology that inquires into the "saving work" of Christ and asks the what, why, and how of redemption as understood by Christians. In this ... survey and ... analysis of two thousand years of Christian reflection on salvation, [the author] lays bare the rich, diverse, and even competing understandings of salvation, their social context and development, and their strengths and weaknesses. Concentrating on thirteen of the most important figures in that long arc --- from its biblical roots to its most controverted contemporary expressions -- [the author] unfolds the thought of each theologian as articulating a distinctive story of salvation or atonement.-Back cover.